2020
DOI: 10.3389/fnmol.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Tau-Mediated Dysregulation of Neuroplasticity and Glial Plasticity

Abstract: The inability of individual neurons to compensate for aging-related damage leads to a gradual loss of functional plasticity in the brain accompanied by progressive impairment in learning and memory. Whereas this loss in neuroplasticity is gradual during normal aging, in neurodegenerative diseases such as Alzheimer's disease (AD), this loss is accelerated dramatically, leading to the incapacitation of patients within a decade of onset of cognitive symptoms. The mechanisms that underlie this accelerated loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 291 publications
0
10
0
Order By: Relevance
“…Astrocytes play major roles in various pathological conditions in the brain due to their key functions in hemostasis, maintenance, and glutamate uptake. Recently, astrocytes were demonstrated to undergo specific modes of activation depending on the pathological conditions in the brain ( Liddelow and Barres, 2017 ; Hinkle et al, 2019 ; Koller and Chakrabarty, 2020 ). A1 astrocytes are induced by pro-inflammatory microglia, express specific markers such as C3 and are associated with various pathological conditions including neurodegenerative diseases and aging ( Liddelow et al, 2017 ; Clark et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes play major roles in various pathological conditions in the brain due to their key functions in hemostasis, maintenance, and glutamate uptake. Recently, astrocytes were demonstrated to undergo specific modes of activation depending on the pathological conditions in the brain ( Liddelow and Barres, 2017 ; Hinkle et al, 2019 ; Koller and Chakrabarty, 2020 ). A1 astrocytes are induced by pro-inflammatory microglia, express specific markers such as C3 and are associated with various pathological conditions including neurodegenerative diseases and aging ( Liddelow et al, 2017 ; Clark et al, 2019 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Altered synaptic structure and function are well-established in AD (Spires-Jones and Knafo, 2012;Pozueta et al, 2013;Chabrier et al, 2014;Price et al, 2014;Mango et al, 2019;Koller and Chakrabarty, 2020). The highest-ranking hippocampal gene, PFN1 (Figure 6A and Table 1), encodes an actin-monomer binding protein that is known to regulate the cytoskeleton of neurites (Murk et al, 2012), but has also been shown to support the highly mobile F-actin in astrocytic projections that surround synaptic clefts (Schweinhuber et al, 2015).…”
Section: Multiple High-ranking Genes Influence Synaptic Structure Thrmentioning
confidence: 99%
“…The notion that glial cells are important to maintaining memory circuits is far from unfamiliar given their role in sustaining excitatory-inhibitory balance in the brain through regulation of extracellular glutamate and GABA levels (Fellin et al, 2006;Henstridge et al, 2019;Mederos and Perea, 2019). Indeed, other have emphasized the role of glial cells in mediating tau-induced impairments of neuroplasticity (Koller and Chakrabarty, 2020). For instance, astrocytic Gs-coupled signaling controls long-term memory independent of learning via astrocytic Adora2A receptors.…”
Section: Trem2mentioning
confidence: 99%
“…Excessive levels of pTau may initiate a positive feedback loop leading to further phosphorylation of tau (Wei et al, 2018). Though knockout of tau generally has no effect on spatial memory (Ke, 2012 #1002} agedependent short-term memory deficits have been reported (Biundo et al, 2018) and the prevailing view is that tau contributes to plasticity events; a process that turns awry and toxic in tauopathies (Biundo et al, 2018;Koller and Chakrabarty, 2020). There are several other mechanisms by which tau could impact synaptic plasticity (see Sotiropoulos et al, 2017) but particularly interesting are those that might occur under the direction of Aβ.…”
Section: Hyperphosphorylation Of Taumentioning
confidence: 99%